Synthesis and characterization of carboxymethyl cellulose with high degree substitution from Vietnamese pineapple leaf waste - Thi Dieu Phuong Nguyen; Nhu Thi Le; Tien Manh Vu; Truong Sinh Pham; Thi Dao Phan; Ngoc Lan Pham; Thi Tuyet Mai Phan (Vietnam Journal of Science, Technology and Engineering, 2022)
One of the most popular derivatives produced by carboxymethylating cellulose’s hydroxyl groups is CMC. The use of CMC as a binder, thickening additive, film maker, suspending aid, and biodegradable substance has a lot of promise. Cellulose was first swelled in a NaOH solution to produce CMC, and then it was treated with monochloroacetic acid in alcohol. In this work, cellulose was successfully extracted from pineapple leaf waste by 0.75 M NaOH at 90oC and 5 M HNO3 at 70oC for 1.5 h and 5 h, respectively. The obtained cellulose fibres, with average diameters of 150-300 nm, were converted to carboxymethyl cellulose (CMC) by esterification. The pure cellulose was soaked in a solution mixture of isopropanol and NaOH for 2 h. It was then reacted with chloroacetic acid (MCA) at 60oC for 1.5 h. The optimum conditions for carboxymethylation were found to be 5 g cellulose, 1.5 g MCA, and 15 ml 16% w/v NaOH. The obtained CMC had a high degree of substitution (DS) of 2.3. The properties of CMC were determined.